The converting sea: Religious change and cross-cultural interaction in the early modern Mediterranean - Clines, Robert John (History compass, 2019)
This review article explores conversion, construed as any change that fundamentally recalibrated the religious, political, and cultural landscape of the early modern Mediterranean. By expanding the concept of conversion to include shifts in collective identity construction, institutional anxieties, literary culture, intellectual traditions, and the visual arts, we can approach a more lucid understanding of the processes of religious change, acculturation, and cross-cultural interaction in the early modern Mediterranean. We can then speak of the early modern Mediterranean as a converting sea: one that shaped the lives of its inhabitants who in turn shaped the cultural landscape of the Middle Sea itself.